Lutzomyia longipalpis is a Species Complex: Genetic Divergence and Interspecific Hybrid Sterility among Three Populations - Lanzaro, Gregory (1993)
The sand fly Lutzomyia longipalpis is the vector of Leishmania donovani chagasi in Latin America. An analysis of genetic variability at 27 enzyme coding loci among three laboratory populations of Lu. longipalpis revealed substantial genetic polymorphism. Levels of genetic distance between all pairwise comparisons of colonies were very high, and consistent with those previously reported among separate species in the genus Lutzomyia. Between 7% and 22% of the loci studied were diagnostic for any two of the colony populations. Experimental hybridization between colonies resulted in the production of sexually sterile male progeny. Our results provide strong evidence that Lu. longipalpis exists in nature as a complex of at least three distinct species. The possible effects of colonization on the genetic makeup of laboratory populations is considered in extending our results to natural populations.